Visualizing databases through an interactive scalable vector graphics chart using extensible markup language technologies - Cabazares, Keno Rojo Lazarus T. (2010)
Presenting in graphical form rather than in textual formal are often state. That means the visualization of the values no longer represent the data once the data has changed. These graphs and charts are also often presented in raster format, which has reduced quality when the image is resized. The study will develop two modules that enable the user to present data in an interactive graphical format using SVG. This would enable the user to easily and efficiently analyze statistical information. The system was developed to enable on module to retrieve data from a database without additional user input, thus enabling the modules to automatically update the information as the data in the database changes. The SVG image is interactive allowing multiple graphs to be created and links between graphs possible